Haiti : Poverty Reduction Strategy Paper: Progress Report. (IMF Staff Country Reports; Country Report ;, 2012)
The progress report on Haiti's Poverty Reduction Strategy Paper is discussed. The Action Plan for National Recovery and Development of Haiti has been presented to the international community at the United Nations conference in New York in March 2010. The plan presents immediate responses to the losses and damage caused by the earthquake, but also outlines a number of key initiatives for creating the conditions to tackle the structural causes of Haiti's underdevelopment. Policies and measures have been adopted to maintain domestic and external monetary stability by lowering the inflation rate, controlling monetary financing, and having a stable exchange rate.